Quality Characteristics of Low-salt Chicken Sausage Supplemented with a Winter Mushroom Powder - Jo, Kyung (Korean J Food Sci Anim Resour, 2018)
Chicken meat is a low-fat and high-protein food and consumption of chicken meat has been increasing globally. Various food ingredients are widely added for their specific purpose to processed chicken meat. Nonetheless, concerns about the association between high sodium intake and various diseases as well as negative perceptions of artificial additives are increasing. Therefore, in meat products, it is necessary to reduce the amount of salt and to replace artificial additives with natural ingredients. Our aim was to investigate the quality characteristics of low-salt chicken sausages manufactured with the addition of a winter mushroom powder. Sausages was manufactured with sodium pyrophosphate (0.3%) or winter mushroom powder (0%, 0.5% and 1.0%) to ground chicken breast. As a result of addition of the winter mushroom powder to low-salt chicken sausages, pH of the meat batter increased, and the proportion of jelly and melted fat exuded from sausages was reduced. The texture of sausages was softened and lipid oxidation in sausages was inhibited by the winter mushroom powder. This powder did not negatively affect the color and sensory properties of the sausages. According to the results of this study, the winter mushroom powder can serve as a natural ingredient to improve quality of low-salt chicken sausages.